Exposure to tris(2,4-di-tert-butylphenyl) phosphate during adolescence induces testicular toxicity in mice: Autophagy-apoptosis interplay - Xiangxiang Chen; Lihua Feng; Yanan Xia; Haoneng Li; Faqun Liu; Yang’e Li; Hengyi Xu; Yang Liu (Ecotoxicology and Environmental Safety)
Tris(2,4-di-tert-butylphenyl) phosphate (AO168 = O), a novel organophosphate ester, has been widely utilized and is commonly exposed in various industries, posing significant threats to both ecological systems and public health. Adolescents are in a pivotal stage of development and are probably more susceptible to the effects of AO168 = O. In this experiment, 4-week-old male mice were given AO168 = O by daily gavage at doses of 0, 0.7, 7, or 70 μg/kg for 28 days. Then, we took the testes as the research subject and delved into the effects of exposure to AO168 = O during the developmental stage on male reproduction. The results demonstrate that AO168 = O can induce both reproductive and developmental toxicity in adolescent mice, manifesting as testicular structural damage, hormonal disturbances, and spermatogenic impairment. Further research suggested that AO168 = O triggered testicular autophagy by inducing oxidative stress, and finally, the interaction between autophagy and apoptosis resulted in testicular toxicity. Additionally, we found that one potential mechanism by which AO168 = O induces interplay between autophagy and apoptosis in testicular cells may involve activation of the ROS/JNK/Bcl-2 signaling pathway. This study clarifies that AO168 = O induces adverse effects in the male reproductive system during adolescence, highlighting specific reproductive risks in adolescents and providing scientific grounds for systematic health risk assessment.